Cephalic tetanus presenting with bilateral facial palsy. Issue 3 (August 2019) - Tahir, A; Pokorny, P; Malek, N
We discuss the case and differential diagnoses of an elderly man who presented with bilateral facial palsy. He had injured his forehead in the garden during a fall on his face and the open wound was contaminated by soil. He then presented to the emergency department with facial weakness causing difficulty speaking. The penny dropped when he started developing muscle spasms affecting his lower jaw a day after admission. It also became clear that he could not open his mouth wide (lock jaw). The combination of muscle spasms and lock jaw (trismus) made tetanus the most likely possibility, and this was proven when he had samples taken from his wound and analysed under the microscope, which showed Clostridium tetani bacilli. C. tetani spores are widespread in the environment, including in the soil, and can survive hostile conditions for long periods of time. Transmission occurs when spores are introduced into the body, often through contaminated wounds. Tetanus in the United Kingdom is rare, but can prove fatal if there is a delay in recognition and treatment.